Luther in Context: With Illustrations. Issue 2 (June 2017) - Wengert, Timothy J.
Abstract: The author explores his work on the first volume of The Annotated Luther detailing Luther's commitment to humanism's "good letters" and his developing theology of preaching law and gospel, especially indicated by the Ninety‐five Theses and Freedom of a Christian .